Optimisation of the preparation phase for orthopaedic surgery: Study protocol for a student-led multimodal prehabilitation feasibility trial (BoneFit) - Lee Ingle; Joanna Snook; Lois Smith; Ben Oliver; James Bray; Liz Wells; Jaswinder Moorhouse; Lili Dixon; Phillip Simpson; Selen Osman; John Saxton; Aarthi Rajendran; et al. (PLoS ONE, 2025)
Background Since the Covid-19 pandemic, a surgical backlog for total hip replacement (THR) and total knee replacement (TKR) surgery remains in the United Kingdom. Multimodal prehabilitation pathways (encompassing exercise, nutritional support and psychological wellbeing) can be utilised to ‘optimise” physical and mental resilience prior to the challenge of surgical intervention. BoneFit is an open-label, non-randomised feasibility trial to determine the recruitment and attendance/adherence rates, delivery and implementation challenges, fidelity, acceptability, and safety of a student-led multimodal prehabilitation intervention in people listed for THR/TKR surgery. We will also determine participant and clinician views of the intervention, and identify any challenges and enablers of inter-institutional partnership working. Methods Individuals listed for THR/TKR surgery aged between 18 to 75 years will be assigned to an intervention (n = 25) or usual-care control group (n = 25). The primary outcome measures will be feasibility of delivering the BoneFit intervention. Physical, psychological, quality of life and clinical outcomes will be assessed at three major time-points; T1 (baseline; 2 months from surgery), T2 (2–10 days from surgery), and T3 (3 months following surgery). We aim to show that the trial is feasible and that we can identify a signal of efficacy based on clinical outcomes collected compared to controls. The study was ethically approved by the Health Research Authority (London Bridge Research Ethics Committee: REC reference: 24/PR/0092) in March 2024. Discussion The development of a multimodal prehabilitation pathway could improve the physical and mental resilience of individuals awaiting orthopaedic surgery. We aim to determine if this translates to faster discharge and reduced complication rates, thus helping boost surgical throughput and potentially easing surgical backlog. It is likely that the concept of ‘waiting’ lists for surgery should be challenged, rather, individuals should be encouraged to use the time available to ‘prepare’ for surgery. Trial registration Registration details ClinicalTrials.gov registration number: NCT06341920.